STUDENTS’ ERRORS USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT AT FOURTH SEMESTER OF ENGLISH LANGUAGE STUDY PROGRAM OF KHAIRUN UNIVERSITY - Nurbalisa M Zen; Saiful Latif; Asrul M Syawal (Universitas Khairun, 2021)
The purpose of this study was to identify the most dominant student errors and to find out the types of errors made in the fourth semester of Khairun University. In collecting data, the researcher used an instrument in the form of a test. The subjects of this study were students of class B in the fourth semester of Khairun University, totaling 15 people. In analyzing the data, the researcher used qualitative methods as research methods. The researcher collects data from students' writing products and then the data is analyzed by Surface Strategy Taxonomy. The researcher identified and classified the types of errors in the use of the simple present tense in writing descriptive texts by students, to find out which errors were the most dominant. The results showed that the students' total errors were 85 errors. The students made errors in omissions of 25 (29.41%), 24 additions (28.23%), 6 sequence errors (07.14%). Based on the results of the study, it was found that the most dominant student error was the formation error of 30 items (35.51%).